Performance of Asphalt Mixtures Modified with Nano-Eggshell Powder - Zghair Chfat, A. Hadi; Yaacob, Haryati; Mohd Kamaruddin, N. H.; Al-Saffar, Z. Hazim; Jaya, R. Putra (Salehan Institute of Higher Education, 2024)
Primary issues in pavement engineering, such as rutting, moisture damage, and fatigue cracking, have prompted numerous studies aimed at improving pavement performance. Utilizing biomaterial waste to modify bitumen through nanotechnology is a promising approach to improve asphalt-mixture properties and aligns with goals of sustainability and reducing the dependence on non-renewable resources. Therefore, the primary objective of this study was to investigate the effect of nano-eggshell powder (NESP) as a sustainable bio-modifier for bitumen on the mechanical properties of asphalt mixtures. To achieve this, asphalt mixtures containing 0% (control), 5%, and 9% NESP were developed, and their mechanical properties were investigated through various tests such as moisture damage, Marshall immersion stability, resilient modulus, dynamic creep, double-punch shear, water immersion, and wheel tracking. The results showed that NESP reduced the moisture susceptibility of the mixtures by increasing their tensile strength ratio. Additionally, the durability of the asphalt mixtures improved as the NESP content was increased. Moreover, the addition of NESP significantly enhanced the resilient modulus and dynamic creep of the asphalt mixtures. The double-punch test revealed that the NESP improved the rutting and fatigue resistance of the asphalt mixtures. Furthermore, the water-immersion test indicated that NESP enhanced the adhesion properties between the bitumen and the aggregate. Finally, the wheel-track test results suggested that the mixtures modified with NESP exhibited a lower rut depth than the control mixtures. Notably, 9% NESP was optimal for enhancing the mechanical properties of the asphalt mixture. The study demonstrated that using NESP as a bio-modifier for bitumen is feasible and offers a more sustainable alternative to traditional bitumen additives. Doi: 10.28991/CEJ-2024-010-11-016 Full Text: PDF